THE IMPACT OF THE GREEN ECONOMY ON SUSTAINABLE DEVELOPMENT IN THE ABRIC COUNTRIES - Rusiadi, Rusiadi; Adivia, Aliza; Yusuf, Mohammad (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
The purpose of this study is to determine how the variables CO2 Emissions, Green Technology, Green Credit, Income Level, Energy Consumption, and Renewable Energy affect Buildings with High Roofs and Buildings with Low Roofs in ABRIC countries. The method of analysis used is called SUR. This study uses data from the World Bank Data website for the study period of 2005–2022 (data years) and data from the CEIC for the study period of 2020–2022 (data months). The results of the SUR analysis show that increasing energy consumption and green-credited payback rates can boost economic growth; however, in order to promote green building, we can increase CO2 emissions and use low-tech technology, which can be seen in every study nation.